Perspectives on Neuroradiology Medical Expert Testimony: Fact and Fiction - Yousem, D.M.; Zoarski, G.H.; Mark, A.S.; Schwartz, E.S. (American Journal of Neuroradiology, 2018)
SUMMARY: There are numerous misconceptions about serving as a medical malpractice expert witness. By maintaining an objective perspective based in the unbiased interpretation of the images provided (for both sides of the conflict), one can best serve society as a whole. Most cases for which a neuroradiology expert is recruited are the following: 1) not with the radiologist as a defendant, 2) resolved without court testimony, and 3) short-lived if frivolous. One can learn much about medicine, our nonradiology colleagues, and the litigation process by participating as an expert witness.ACRAmerican College of Radiology